Kajian Potensi Penerapan Teknologi Smart Airport di Bandara Internasional Soekarno-Hatta Jakarta Indonesia - Burhanuddin Hanantyo; Tony Dwi Susanto (Labkat Press KA FTIK UNIKOM, 2022)
The COVID-19 pandemic at the beginning of 2020 had a huge impact on the aviation industry, especially the airport industry. The emergence of the concept of 'New Normal' or new habits has an impact on the adjustment of airport services in Indonesia. Literature studies conducted at airports in developed countries such as Germany, the United States, Finland and Japan that have implemented several Smart Airport Technologies such as Parking Robots, Indoor Navigation, Automatic Desk Check In, Facial Recognition, Humanoid Robots and proven to be able to increase user satisfaction airport services. The purpose of this study is to explore potential opportunities for implementing Smart Airport Technologies at Soekarno-Hatta International Airport, Jakarta, Indonesia by conducting several analysis of existing conditions and benchmarking against airports in developed countries that have successfully implemented Smart Airport Technologies. In achieving the objectives of this study, the literature study method was used. The literature study used in this journal comes from various international journals that discuss Smart Airport Technologies which are proven to be able to increase airport service user satisfaction. The results of this study are practical contributions in the form of the emergence of Smart Airport Technologies Solutions and can be a recommendation to Soekarno-Hatta International Airport Jakarta Indonesia in implementing Smart Airport Technologies in the future. In terms of scientific contributions that can be generated in this research, namely as a Blueprint Guideline for the airport industry in Indonesia in implementing Smart Airport Technologies. This research has limitations where the object of research used is only Soekarno Hatta Airport, in further research the object of research can be expanded at other airports in Indonesia that want to implement Smart Airport Technologies.